Phase Sensitive Parametric Interactions in a $Ga_{0.5}In_{0.5}P$ Photonic Crystal Waveguide - Amnon Willinger; Aude Martin; Sylvain Combrie; Alfredo De Rossi; Gadi Eisenstein (IEEE Photonics Journal, 2016)
We report phase sensitive amplification in a $1.5\mathrm{\,mm}$ long, $Ga_{0.5}In_{0.5}P$ dispersion engineered photonic crystal waveguide which has a flattened dispersion profile. A signal degenerate configuration with pulsed pumps whose total peak power is only $\text{0.5}\,\text{W}$ yields a phase sensitive extinction ratio of $\text{10}\,\text{dB}$ .